TEACHER IDENTITY AS A ROOT OF TEACHER SELVES: PROFESSIONAL IDENTITY VS PERSONAL IDENTITY - Yohana Ina Triana Weran; Paulus Kuswandono (Journal of English Educational Study (JEES), 2021)
This paper sought to investigate the relationship/gap between personal and professional identity experienced by a group of elementary school teachers in Sintang, West Borneo. In gathering the data, the researchers used questionnaire and divided it into two parts: close-ended statements in a form of Likert Scale and open-ended questions which asked the opinion of the teachers related to their personal and professional identity. This study employed a qualitative research, using the snowball sampling. The researchers distributed the questionnaire in form of Likert scale and continued it with open-ended questions. The questionnaire was then followed up by individual interview. The questions were posited to identify teachers’ beliefs of their professional and personal identity. The research results reveal that there are five gap points between personal and professional identity within teacher, namely adjusting myself to the work place, trying to be a good parent, class situation and students’ characteristic, cannot be ‘me’ when in the classroom, and professional identity affects personal identity. Recommendations for further research studies are also provided at the end of this paper